Facies Models Revisited: An Examination of Quantitative Methods - Harper Jr., Charles (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1984)
Summary In the widely-read Geoscience Canada Facies Models volume, Walker (1979) advocates a method for constructing facies models based on transition frequencies (see also Harper, 1984). I here discuss modifications to Walker's method, pitfalls both to Walker's and related methods, and suggest improvements, especially the use of median tetrads (defined below) and half-normal plots to recognize significant facies transitions "masked" by other approaches.